Influence of climatic changes on respiratory health in a teaching herd of outdoor-housed horses - Calomeno, Stefano Strano; Freitas Santi, Thasla de; Barbosa, Bianca; Weber, Saulo Henrique; Oliveira, Tiago Marcelo; Machado, Gisele Fabrino [UNESP]; Michelotto, Pedro Vicente (Elsevier, 2024)
Horses maintained outdoors may experience a lower-allergenic environment compared to their stabled counterparts. This study hypothesizes that climatic changes in southern Brazil can influence respiratory status. To test this hypothesis, we evaluated the lower airways of 17 horses from a teaching herd in southern Brazil, maintained outdoors, during winter, spring, and summer. Except for one mare with a history of severe asthma, all horses were considered healthy and underwent a physical examination. Airway endoscopic evaluation included scoring for tracheal mucus (0-5) and bronchial septum thickness (1-5). Bronchoalveolar lavage fluid (BALF) was collected at three time points, while bronchial septum biopsies were performed during spring and summer for airway epithelial investigation. Data analysis involved repeated measures ANOVA and Wilcoxon tests (p < 0.05). Tracheal mucus score and septal thickness did not differ across investigation periods. In BALF cytology, the mean percentage of neutrophils was higher in spring than summer (7.9 ± 13.4 % vs. 4.5 ± 11.7 %, P = 0.037), and eosinophil count was higher in winter than spring (0.64 ± 1.29 % vs. 0.03 ± 0.13 %, P = 0.034) and summer (0.64 ± 1.29 % vs. 0.14 ± 0.60 %, P = 0.023). Histopathological observations showed no differences between time points, and no correlations were observed with BALF analyses (P > 0.05). This study demonstrates that, even in an outdoor environment, horses' airways exhibit cytological modifications associated with different seasons, indicating a need for deeper investigation; endobronchial biopsy did not contribute to the clinical diagnosis.